Analisis Tingkat Partisipasi Masyarakat Dalam Pemilihan Kepala Desa Orahili Kecamatan Pulau-Pulau Batu Kabupaten Nias Selatan - Falua Jisokhi Haluana'a; Irwan Nasution; Beby Masitho Batubara (Universitas Medan Area, 2020)
Participation of people are needed to have political participation in the village’s election. Because participation are means for development and proceeded to the political democracy. The subject in this study is “ how participates society in the village elections in the village of Orahili village” and “ Any factor of what drives society can participate in the head of the village election in Orahili village in 2014”. Research results and discussion explains the participation at Orahili village very high participation in the village’s election activities, the first conclution that level of awareness community begins to grow and the second, people are looking for an experienced leader in government to be sure to smister and serve the public without limit.